A participação das crianças no retorno das aulas presenciais da Educação Infantil: elementos para pensar a democracia - Silva, Rafael Araújo da (2022)
The civic invisibility of children persists in the current times and the environments of early childhood education do not escape from this reality. Discussing the right of participation of children is necessary to break the paradigm of the silencing of this social group. This scenario is aggravated at a time of crisis caused by the COVID-19 pandemic, through which a series of measures were taken, radically changing everyone's lives, including that of children and the daily routine of early childhood education. Given this panorama, aimed to analyze the ways in which children's participation occurs in the return to classes in an institution of Preschool Education in the midst of the pandemic period. To develop the research, the theoretical framework was based on studies on Democracy and Participation, by authors such as Comparato (2010), Bobbio (2000), Hart (1992), the Sociology of Childhood with authors such as Sarmento (2007), Fernandes (2005) and Campos and Fernandes (2012), the Pedagogy of Childhood, with authors such as Oliveira-Formosinho (2007), the Reggio Emilia proposal, Edwards, Forman and Gandini (1999), Louro (2014) and Lino (2013), and the Modern of Portugal School, Niza (1998) and Bohac (2014). The methodological approach of the research was qualitative, with inspiration in Ethnography and research with children. The methodological procedures also included the analysis of documents related to Early Childhood Education in the municipality of Currais Novos - RN, they were: Municipal Education Plan (2015 - 2025), Pedagogical Political Project of the investigated Early Childhood Education institution, and the School Diary of the class's titular teacher. The investigated children were 5 years old, resided in the municipality of Currais Novos/RN, and were in level V of Early Childhood Education. The on-site research took place in the second semester of the year 2021, when classes were returning to the classroom format after a long period of suspension, with observations, interviews with the children and their guardians, and interviews with a representative of the Municipal Secretary of Education of the city of Currais Novos/RN. As a result of the intertwining between theory and empirical research, three analytical categories were elaborated, entitled: 1) Childhood Education Institution as a fostering agent of children's participation; 2) Children's participation: interaction and subversion; and 3) Non-participation of children in a Childhood Education Institution. As a result, it was possible to evidence that there is a participative prism of the child, in which the more distant the children are from the decision centers, such as the Municipal Secretary of Education, the lesser are their possibilities of participating and the lesser is their power to influence the decisions. On the other hand, the closer the children are to the decision making instances, the greater is their possibility of participating in some way in the decision making, whether through interaction or subversion. Furthermore, it was possible to verify that there are still many situations in the scope of Early Childhood Education in which children do not participate, prevailing attitudes of silencing the child by the adult (intentionally or not) as a natural and even institutionalized practice.